Age, growth and mortality of the European Seabass, (Dicentrarchus Labrax) in Bardawil lagoon, North Sinai, Egypt - Menna O El-Desoki; Younis M Younis; El-Dakar A Youssef; Salem M Ahmed; Kassem S Ahmed; Ahmed M Al-Beak (International Journal of Aquaculture and Fishery Sciences - Peertechz Publications, 2021)
Age, growth, and mortality of European Seabass (Dicentrarchus labrax) were studied from a small-scaled fishery of Bardawil lagoon, (North Sinai, Egypt). 181 specimens (16.6 to 35 cm total Length and 39.8 to 367.2 g total weight). The relationship between length and weight was W = 0.0054L3.1428. Age was determined by otoliths and age groups I to IV years were observed. Growths in length and weight at the end of each year were calculated. The growth parameters of von Bertalanffy equation were calculated as (L∞ = 48.69 cm, K = 0.1677 yr -1 and t0 = -0.447 yr -1). Growth performance index was calculated (φ = 2.60 for length and 1.25 for weight). Mortality rates were 0.867 yr-1, 0.25 yr1and 0.617 yr-1 for total, natural and fishing mortality, respectively. The currently exploitation rate E = 0.712 yr-1 indicating that, the population of this species is being heavily exploited.